Spatial Images in Nominations of Feelings of Disgust and Rejection (on Material of Russian Dialect Lexis) - Y. V. Malkova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The results of the analysis of motivational models underlying Russian dialect and national vocabulary and phraseology with the meaning of disgust and rejection are presented. Those lexical units are selected that are based on spatial images. In the course of the research the semantic-motivational reconstruction of lexemes and phraseological units and ethno-linguistic interpretation of the obtained results are carried out. The author shows that the feeling of disgust and rejection, according to the language, occurs and proceeds in certain organs of the human body. Most often, the place of concentration of the studied states are the heart and soul , which in naive anatomy are closer to the digestive organs. Participants in the prototypical situation of rejection also fit into the spatial coordinates. Conceptualization of conceptual meanings takes place taking into account the axiological marking of space existing in culture. The main motives are the idea of moving away from the object of rejection (a native speaker exploits the meanings of ‘turn away’, ‘move away’, ‘pass by’) and the idea of interrupting any kind of contact with it (visual, tactile). It is argued that the symbolic spatial images carry the idea of conflict, dissimilarity of the subject and the object of feelings. The author pays attention to the interpretation of language data from the point of view of ideas about social relations in traditional society. The reconstruction of the prototypical situation of disgust and rejection is carried out.